Pengaruh Profitabilitas, Leverage, Firm Size, Dan Likuiditas Terhadap Harga Saham: Studi Empiris Pada Perusahaan Sub Sektor Pharmaceuticals & Health Care Research - Azizah Rachmah Zahrani; Astrid Dita Meirina Hakim (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to determine the partial influence of Profitability, Leverage, Firm size and Liquidity on Stock Prices in the Pharmaceuticals & health care research sub-sector listed on the Indonesia Stock Exchange for the period 2019 - 2023. The sample for this research is 7 companies in the Pharmaceuticals & Sub-sector. health care research listed on the Indonesia Stock Exchange for the 2019-2023 period. This research uses panel data regression statistical analysis tools assisted by the Eviews version 12 program and Microsoft Excel 2016. The results of this research show that Profitability, Leverage and Firm size partially have no effect on Stock Prices. However, liquidity partially and significantly influences share prices.